Pengembangan Kurikulum Terintegrasi DI Sekolah/Madrasah - Rahman, Khalid (J-PAI: Jurnal Pendidikan Agama Islam, 2014)
The procedures and attributes are must fulfilled to integrated curriculum development of schools or madrasah that consist: (1) the concept of integrated curriculum development is conducted at SMAN 10 Malang, consists of the integrated conception of vision and mission, institutionalintegration, the integration of curriculum and learning by models that are suitable to within single disciplines, across several disciplines, and inside the mind of the learner; (2) planning of integrated curriculum that is used the rational-interaction model, and deductive rational model to divide roles between the principal of school and the teachers, and toorganize educational components that are supporting the integrated curriculum development; (3) implementation for integrated curriculum is carried out with the learning process in classroom, that prioritize the methods of problem solving, project methods, teaching units, inquiry, discovery, thematic approach, media of learning and sources of learningthat are varied; (4) evaluation for integrated curriculum is conducted with control function and supervision by the principal, while the teachers assess students that is based on three domains, namely cognitive, affective and psychomotor, then all of domains are manifested to form of test instruments and non-test.keywords: Curriculum Development, Integrated Curriculum